Frequency of E-cigarette and Cigarette Smoking and Associated Health Symptoms among the Youth - Khan, Laraib; Khan, Fatima; Parmani, Nisha; Fatima, Kanza; Hamza, Ali; Khalid, Umer; Asif, Ahmed; Asad, Ahmad Subhan (International Journal of Health Sciences, 2024)
Purpose: To determine the prevalence of e-cigarette and traditional cigarette use among Pakistani youth and to identify the associated health symptoms. Methodology: This cross-sectional study was conducted using a sample size of 178 respondents aged 15-25, selected through non-probability convenience and snowball sampling methods. Data were collected over five days (1st September 2023 to 6th September 2023) using a questionnaire adapted from validated studies (GATS and YUPESS) and distributed via Google Forms. Findings: The study population consisted of 178 respondents, with a gender distribution of 72.1% males and 27.9% females. Among the respondents, 41.2% had tried either e-cigarettes or traditional cigarettes. The age of first smoking experience varied, with many trying their first cigarette between ages 15 and 18. Significant health symptoms associated with smoking included respiratory issues, general malaise, and worsened asthma. Unique Contribution to Theory, Policy and Practice: The research highlights the prevalence and health impacts of e-cigarette and traditional cigarette use among Pakistani youth. It underscores the need for targeted public health interventions and stricter regulations to mitigate these health risks.